Economic development of communist China - "Li , Choh-Ming" (Berkeley, 1959)
This work is neither a general survey nor a historical study of the Chinese economy, but an economic analysis of its growth from 1952 to 1957. Virtually all quantitative and qualitative information was derived from Chinese-language sources published in Peiping up to the last quarter of 1957.
Keywords: Economics